2017
DOI: 10.1111/jns.12234
|View full text |Cite
|
Sign up to set email alerts
|

Markers for Guillain‐Barré syndrome with poor prognosis: a multi‐center study

Abstract: Guillain-Barré syndrome (GBS) is an acute monophasic neuropathy. Prognostic tools include the modified Erasmus GBS outcome score (mEGOS), Erasmus GBS respiratory insufficiency score (EGRIS), and the increase in serum IgG levels (ΔIgG) 2 weeks after intravenous immunoglobulin (IVIg) treatment. Given that proportions of GBS subtypes differ between Western countries and Japan, the usefulness of these tools in Japan or other countries remains unknown. We enrolled 177 Japanese patients with GBS from 15 university h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 20 publications
4
53
4
1
Order By: Relevance
“…Our results were consistent with findings from another Asian cohort in Japan . In comparison to the Japanese study, the mean mEGOS on admission (4) and day 7 of admission (5) in our cohort were higher than the Japanese patients (3 and 4, respectively).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results were consistent with findings from another Asian cohort in Japan . In comparison to the Japanese study, the mean mEGOS on admission (4) and day 7 of admission (5) in our cohort were higher than the Japanese patients (3 and 4, respectively).…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, we also found EGRIS useful in our GBS population. Our findings were in keeping with the Japanese study, which found GBS patients with a higher score on EGRIS were more likely to require mechanical ventilation. Early identification of GBS patients in need of respiratory support is crucial as it allows treating clinicians to alert intensive care specialists and measures can be taken to escalate management to the intensive care unit where elective intubation could be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mEGOS has very good predictive power (Area Under the Receiver Operating Characteristic [ROC] Curve [AUC] = 0.87) for prediction of outcome after 4 weeks, indicating very good discriminative ability. The mEGOS was recently validated in a Japanese cohort and performed equally good in this cohort, underlining the validity of the model . In the Second IVIg Dose‐Guillain‐Barre syndrome (SID‐GBS) trial an mEGOS score of at least 6 was used as a cutoff for poor prognosis.…”
Section: Methodsmentioning
confidence: 94%
“…A study of 177 Japanese patients had a mean (SD) mEGOS score at admission of 3.3 (2.4), and at 6 months those who had a mean score of 3 were able to walk independently (89%) while those who had a mean score of 5.5 were unable to do it (11%). They also showed that with cutoffs between 5 and 7, the specificity of mEGOS to predict outcomes increased . This may suggest that most of our patients (66%) would have a more favorable recovery as they had a mEGOS score at admission of <5.…”
Section: Discussionmentioning
confidence: 99%